The political economy of narcotics production, consumption and global markets - Buxton, Julia (Fernwood Publishing [u.a.], 2006)
This scholarly examination of the worldwide web of narcotics today provides students, social workers, health providers, law enforcement officers and policy makers with an up-to-date, overall exploration of the world of drugs. Vast resources are pumped into the 'war on drugs'. But in practice, prohibition has failed. Narcotics use continues to rise, while technology and globalisation have made a whole new range of drugs available to a vast consumer market. Where wealth and demand exist, supply continues to follow. Prohibition has failed to stem consumption and production, criminalised social groups, impeded research into alternative medicine and disease, promoted violence and gang warfare, and impacted negatively on the environment. The alternative is a humane policy framework that recognizes the incentives to produce, traffic and consume narcotics.
Includes bibliographical references and index
Keywords: Drogue, Lutte contre la; Drogues - Trafic; Toxicomanie; Geschichte; Politik; Drug control -- History; Drug abuse -- Government policy; Drug traffic -- Government policy; Rauschgift; Globalisierung